The Life Strategies and Structure of Populations of Tortrix Moths (Lepidoptera, Tortricidae) in Ecosystems of the Exclusion Zone of the Chernobyl Nuclear Power Plant - Drozda, Valentin (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The results of long-term researches about features of formation of life strategies and tactics of the population of tortrix moths in ecosystems of the exclusion zone of the Chernobyl nuclear power plant were presented. The factors are defining of character and specificity of life strategies of tortrix moths on an axis of r- and K-continuum were analyzed. We collected and identified 38 of tortrix moths of garden and forest ecosystems of the exclusion zone. The physiological monitoring of phytophages suggested determination of the mass of pupae, fecundity, and content of lipids in caterpillars of rose tortrix moth. The structure and character of oogenesis of females of rose tortrix moth were researches in detail. The obtained data were compared with similar indicators of tortrix moths of collected in industrial gardens. The level of vitality of tortrix moths of collected in the exclusion zone exceeds significantly indicators of insects from industrial gardens. The expressed activity of native populations of entomophagous, which develops in the exclusion zone with an insignificant manifestation of entomopathogens was noted. The entomopathogens infected more intensively pupae of industrial gardens. This is due to with the physiological condition of tortrix moths. The indicative were materials of physiological monitoring of populations of tortrix moths, which selecting in ecosystems of the exclusion zone. On indicators of the mass of pupae, of the fecundity of females and content of lipids in caterpillars of rose tortrix moth was observed a significant excess of them in comparison with populations, which developing in industrial gardens. The ecological and trophic conditions of ecosystems of the exclusion zone are optimizing vital parameters of tortrix moths, which have developed here.